Evaluation of Blood Culture Results in Patients with Malignancy in Erzurum Province, Turkey - Osman Aktas; Ozgür Akbaba; Muhammet Hamidullah Uyanik; Hakan Uslu (Acta Medica Lituanica)
Background: Bloodstream infections are a serious public health problem that requires follow-up with blood culture; this negatively affects the course of the disease and patient healthcare costs in patients with malignancy. This study aimed to determine the growth frequency of pathogens and their antibiotic resistance profiles in the blood cultures of patients with hematological and oncogenic malignancies.Materials and methods: The results of 7451 blood cultures, obtained from 2926 patients between January 2017 and January 2022, were evaluated retrospectively. Of these cultures, 3969 were obtained from patients with malignancy (diagnostic codes C00-D48 in ICD-10) and 3482 from patients without malignancy. The hospital information management system modules were used to acquire patient data and blood culture results.Results: Various microorganisms grew in 10.1% of blood cultures. Of these organisms, 64.1% were isolated from cases of malignancy. Of the pathogens, 49.2% were gram-negative bacteria, 47.7% were gram-positive bacteria, and 3.1% were fungi. The most frequently isolated bacteria were methicillin-resistant coagulase-negative staphylococci (3.2%), Escherichia coli (2.3%), Klebsiella pneumoniae (1.0%), methicillin-sensitive coagulase-negative staphylococci (0.7%), and Staphylococcus aureus (0.6%). Pathogen positivity was highest in the patient cultures with urinary system cancer (23.9%), thyroid and other endocrine gland cancers (20.6%), female and male genital organ cancers (18.2%/16.9%), and digestive organ cancer (14.2%). Gram-negative bacteria to ampicillin, piperacillin, and sulfamethoxazole-trimethoprim and Gram-positive bacteria to penicillin, erythromycin, and sulfamethoxazole-trimethoprim were highly resistant. Combined resistance to imipenem and meropenem was observed in 25 Gram-negative bacteria. Twelve (48%) of the carbapenem-resistant bacteria were isolated from patients with lymphoid, hematopoietic, and related tissue malignant neoplasia.Conclusion: This study reported microorganisms and their antimicrobial resistance in the blood cultures of malignant patients, a special patient group. It pointed out that the antibiotic resistance of Staphylococcus, Klebsiella pneumoniae, and E. coli is high enough to cause problems in the treatment of patients with malignancy.